MORPHOLOGICAL CHANGES IN THE SALIVARY GLANDS OF RATS UNDER DIET-INDUCED OBESITY - Гордієнко, Л.П.; Єрошенко, Г.А.; Непорада, К.С. (World of Medicine and Biology, 2015)
Obesity is currently regarded as pandemic. According to the literature, obesity and associated pathological conditions lead to a decrease in proper functioning of the salivary glands, and as a consequence to reduction of salivation, increased saliva viscosity and dry mouth. Mulfunctions of the salivary glands are the cause of pathological processes in the organs of the oral cavity and disruption of digestive processes in the other parts of the gastrointestinal tract. However, pathological mechanisms involved in the impact of obesity on salivary glands are not fully established. The aim of the research was to study the morphological changes in the submandibular salivary glands of rats under diet-induced obesity. The study was carried out on white rats kept on high calorie diet during 20 weeks. Keeping on high-calorie diet leads to the development of abdominal obesity in the rats. Morphological studies were performed to evaluate the pathological changes in the salivary glands of rats under diet-induced obesity. It was established the swelling and degenerative changes of acinar epithelial cells in the parenchyma of lobules. The boundaries between cells were not found locally. Cytoplasm was homogeneous and of high optical density, small polymorphic nuclei were placed chaotically in all parts of the cytoplasm. Locally it was observed atrophy of acinar complexes and proliferation of fibrous connective tissue. There were acini polymorphism in size, shape and number of secretory cells and degenerative and necrobiotic changes of it. Preferably adipocytes were identified in the peripheral parts of lobules of submandibular salivary glands. It was impossible to determine the intralobular ducts due to degenerative changes of the epithelium. The basement membrane of interlobular ducts was locally destroyed. The content of the ducts consisted of desquamated epithelial cells and cellular detritus. Arterioles were spasmodic. Venules were dilated, red blood cells densely filled the gap. It was determined a perivascular edema. The number of white blood cells was increased in the perivascular interlobular connective tissue. Lymphocytes, plasmocytes and macrophages formed groups in the stroma around blood vessels and interlobular ducts on the background of the plethora of venules and interstitial edema. Particular attention is attracted by the appearance of mast cells in the interlobular connective tissue of submandibular salivary glands. Most cells were in a state of degranulation. Thus, under diet-induced obesity there are pathological changes in the tissues of the salivary glands such as as degenerative and necrobiotic changes of epithelial cells of intralobular ducts, desquamation of epithelial cells of interlobular ducts, increased collagenogenesis of interlobular connective tissue, venous congestion.